Sistem Informasi Manajemen Jalan untuk Monitoring Beban Lalulintas dan Evaluasi Kinerja Perkerasan - Darmawan, Didit; Chamdani, Maulana (Jurnal Teknik Informatika dan Teknologi Informasi, 2026)
An integrated road management information system was developed to continuously collect vehicle volume, composition, and load data through moving weight sensors. The data allows the calculation of the Equivalent Single Axle Load (ESAL) which is the basis for evaluating the performance of road pavement. This information supports managers in predicting the remaining life of pavement, proactively adjusting maintenance schedules, and allocating repair budgets to the most critical segments. The system also functions as a law enforcement instrument against overloaded vehicles that accelerate pavement damage. Integration with geographic information systems and asset management systems strengthens spatial analysis as well as lifecycle cost calculations. Successful implementation depends on periodic sensor calibration, the availability of skilled personnel, a sustainable funding model, and a modular architecture that supports technology improvements. Real-time data enables dynamic maintenance planning that is responsive to changing traffic patterns. The results of the study confirm that this system is able to increase the effectiveness of road infrastructure management, extend the life of pavement services, and support data-driven decision-making. The practical implication is the need for a strategy of strengthening technical and institutional capacity so that the system can be widely adopted as a modern solution in sustainable road management.